Perception of Supervisory Styles - Schaaf, Stephanie; Liljequist, Laura; Wilson, Randal; Hart, Sharon B. (Seminars in Speech and Language, 2023)
Supervision is a dynamic and challenging leadership process that remains an essential element within the field of speech-language pathology. This study examines a facet of the supervisory relationship and investigates whether supervision styles are similarly perceived by the supervisor and supervisee and if a mismatch in perceptions relates to satisfaction between supervisor–supervisee dyads. Data were collected through completion of a demographic questionnaire as well as the Supervisory Style Inventory, which categorizes supervisory style as being attractive, interpersonally sensitive, task-oriented, or mixed. Findings demonstrate notable variance in the self-reported supervisor style and the style supervisees perceived as being demonstrated with over half (66%) of supervisor–supervisee dyads reporting a perceived mismatch in style. There was not a significant difference in the level of supervisee satisfaction for supervisor dyads reporting a match in style compared with mismatch. Satisfaction was correlated with all three reported style characteristics; however, interpersonal and task-oriented supervisory style characteristics were more strongly correlated with supervisee satisfaction. Having a mixed style was the only style that was significantly correlated with supervisees reporting having their needs met. Discussions include practical implications, limitations of the study, as well as recommendations for future research.
Keywords: supervision; supervisor style; speech-language pathology